Staregi Komunikasi Interpersonal Guru Dalam Membentuk Motivasi Intrinsik Siswa Kelas 3 SDN 67 Kota Bengkulu - Eva Yuliyanti; Reni Kusmiarti (STAI Bumi Silampari, 2025)
This study aims to analyze the use of interactive learning methods in improving learning achievement of grade 3 students of SDN 67 Bengkulu City by using the perspective of DeVito's interpersonal communication theory as the basis of analysis. The theory used is DeVito's interpersonal communication theory which includes five main principles namely openness, empathy, equality, support, and positive attitude as a framework to assess the effectiveness of communication in interactive learning. The research method used a qualitative approach involving a grade 3 teacher (Mrs. Rumlah, S.Pd) and 31 grade 3 students (16 boys and 15 girls) aged 8 to 9 years old as participants. Data collection was conducted through direct observation of the implementation of interactive learning and analysis of changes in communication patterns in the learning process. The results showed that the implementation of interactive learning methods with DeVito's principles resulted in significant changes from teacher-centered communication patterns to student-centered communication patterns. The principle of openness can be seen from the increasing frequency of students asking questions spontaneously and the courage of students to convey difficulties in learning, which ultimately contributes to improving student learning achievement.